Cell studies on Electrohydrodynamic (EHD)-3D-bioprinted Bacterial Cellulose\Polycaprolactone scaffolds for tissue engineering - EKREN, NAZMİ; GÜNDÜZ, OĞUZHAN (ELSEVIER SCIENCE BV, 2019)
The application of three-dimensional (3D) printed scaffolds for tissue engineering have gained significant attention in recent years. The biological activity of scaffolds used in tissue engineering applications depends on fabricating high-resolution patterns with fiber orientation and scale. In this study, Bacterial Cellulose (BC) and Polycaprolactone (PCL) composite scaffolds with the line spacing of 100 mu m are produced using Electrohydrodynamic (EHD)-3D-bioprinting technique. The composite scaffolds exhibit enhanced biocompatibility with facilitated cell attachment and proliferation in vitro. The results of this work have demonstrated that EHD-3D-bioprinting method shows great potential for the preparation of BC/PCL composite scaffold and patterns for tissue engineering with enhanced bioactivity. (C) 2018 Published by Elsevier B.V.
Keywords: EHD-3D-bioprinting; Biomaterials; Polymers; Bacterial Cellulose; Polycaprolactone; IN-VITRO; 3D